The relevance of economic issues at the Belgrade conference - Bettina S. Hass-Hürni (Intereconomics, 1978)
Despite or because of the relatively brief concluding document of the Belgrade follow-up meeting mandated to examine the implementation of the Helsinki Final Act, it is worthwhile to review the proposals made in “Basket II“ (economics) and relate them to the two other “Baskets“ (security and “human rights“) in order to understand the process of détente more thoroughly.
Keywords: 330; Csce